2015
DOI: 10.1002/jwmg.886
|View full text |Cite
|
Sign up to set email alerts
|

Rapid growth and genetic diversity retention in an isolated reintroduced black bear population in the central appalachians

Abstract: Animal reintroductions are important tools of wildlife management to restore species to their historical range, and they can also create unique opportunities to study population dynamics and genetics from founder events. We used non‐invasive hair sampling in a systematic, closed‐population capture‐mark‐recapture (CMR) study design at the Big South Fork (BSF) area in Kentucky during 2010 and Tennessee during 2012 to estimate the demographic and genetic characteristics of the black bear (Ursus americanus) popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
42
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 83 publications
(119 reference statements)
4
42
0
Order By: Relevance
“…Importantly, our results indicate very little genetic drift on Midway's offspring (generations F 1 to F 6 ) within the early years post-release. Rapid population growth after a population bottleneck has been shown to reduce the magnitude of genetic drift (Murphy et al 2015), and indeed this rapid population growth was observed at Midway Atoll (λ = 1.73; Reynolds et al 2008). Allele retention in isolated populations over time is also influenced by the rate of population growth, population abundance, and species' life-history characteristics (Tracy et al 2011).…”
Section: Discussionmentioning
confidence: 95%
“…Importantly, our results indicate very little genetic drift on Midway's offspring (generations F 1 to F 6 ) within the early years post-release. Rapid population growth after a population bottleneck has been shown to reduce the magnitude of genetic drift (Murphy et al 2015), and indeed this rapid population growth was observed at Midway Atoll (λ = 1.73; Reynolds et al 2008). Allele retention in isolated populations over time is also influenced by the rate of population growth, population abundance, and species' life-history characteristics (Tracy et al 2011).…”
Section: Discussionmentioning
confidence: 95%
“…Such apparent Allee effects could dissipate as cubs born at TRC grow older and reach maturity and as more males immigrate to the TRC. Other researchers have documented low initial growth rates of reintroduced bear populations that dramatically increased in subsequent years (Eastridge and Clark , Murphy et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research efforts, such as reintroduction of black bears [15] [16], historic perspectives in managing black bears [12], black bear population estimation [17], and presentations to visitors regarding black bear management have provided a foundation to managerial decision-making. While these efforts have much merit, few focused on assessing residents' perceptions and attitudes toward black bear management in Kentucky [3].…”
Section: Introductionmentioning
confidence: 99%